Biodiversity of the aculeate wasps (Hymenoptera: Aculeata) of the Arabian Peninsula: Chrysidoidea, Embolemidae - Olmi, Massimo (Zootaxa, 2020)
An updated checklist of the Arabian species of Embolemidae is provided here. The list includes a single species: Embolemus harteni Olmi, 1997. Distributions, both on the Peninsula and extra-limital, are provided; this species is not endemic to the Arabian Peninsula.